2021
DOI: 10.3233/jad-201100
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Effects of Aerobic Exercise in Alzheimer’s Disease: A Pilot Randomized Controlled Trial

Abstract: Background: Aerobic exercise has shown inconsistent cognitive effects in older adults with Alzheimer’s disease (AD) dementia. Objective: To examine the immediate and longitudinal effects of 6-month cycling on cognition in older adults with AD dementia. Methods: This randomized controlled trial randomized 96 participants (64 to cycling and 32 to stretching for six months) and followed them for another six months. The intervention was supervised, moderate-intensity cycling for 20–50 minutes, 3 times a week for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 43 publications
0
68
0
5
Order By: Relevance
“…Previously, we have reported that our intervention participants had a smaller increase in global cognition as measured by the ADAS-Cog at 6 months (1.0 ± 4.6) than its natural course (3.2 ± 6.3-point increase; p = 0.001) (Yu et al, 2021). In this study, we found a significant negative correlation between the 6-month declines in hippocampal volume and the 6-month increases in ADAS-Cog, meaning that hippocampal atrophy was significantly associated with cognitive decline during the intervention period.…”
Section: Discussionmentioning
confidence: 57%
“…Previously, we have reported that our intervention participants had a smaller increase in global cognition as measured by the ADAS-Cog at 6 months (1.0 ± 4.6) than its natural course (3.2 ± 6.3-point increase; p = 0.001) (Yu et al, 2021). In this study, we found a significant negative correlation between the 6-month declines in hippocampal volume and the 6-month increases in ADAS-Cog, meaning that hippocampal atrophy was significantly associated with cognitive decline during the intervention period.…”
Section: Discussionmentioning
confidence: 57%
“…Table 1 lists the 26 participants’ baseline characteristics with a mean age (SD) of 77.6 (7.0) years, 65.4%men, a mean (SD) education of 15.4 (3.0) years, and an ADAS-Cog (SD) of 18.1 (7.8). The baseline characteristics of these 26 participants were consistent with the full cohort of the FIT-AD Trial, except that the percent of men were higher (65.4%versus 55%in the 96 participants) [ 16 ].…”
Section: Resultsmentioning
confidence: 86%
“…Another study of the effects of exercise showed improved memory performance and reduced hippocampal atrophy, along with improved cardiorespiratory fitness, in AD patients [ 295 ]. Moderate-intensity cycling may reduce the decline in global cognition in older adults with mild-to-moderate AD dementia [ 296 ]. A meta-analysis study using a random-effects model compared different quantities of physical activity and exercise interventions for AD in detail and concluded that physical activity and exercise can improve cognition in older adults with AD [ 297 ].…”
Section: Lifestyle Modificationsmentioning
confidence: 99%